Manajemen Kurikulum dalam Meningkatkan Mutu Pendidikan di Era Digital di MTs Al Ihsan Kalikejambon Tembelang Jombang - Zuhriyah, Ilhami Aminatu; Sirojudin, Didin; Chotimah, Chusnul (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
Curriculum management is an activity related to educational management which begins with planning, organizing, implementing, and evaluating the curriculum to achieve agreed goals, both short, medium and long term. The objectives of this research are: (1) To find out curriculum management in improving the quality of education in the digital era at MTs Al Ihsan Kalikejambon. (2) Knowing the school’s efforts to improve the quality education in the digital era at MTs Al Ihsan Kalikejambon. (3) Knowing the supporting and inhibiting factors in implementing curruculum management in the digital era at MTs Al Ihsan Kalikejambon. The research method used was descriptive qualitatif. Data collection was carried out through observation, interviews, and documentation. Based on research conducted, MTs Al Ihsan Kalikejambon Tembelang Jombang has demonstrated a strong commitmen to digital era curriculum management by utilizing digital assessments, incorporating, tehcnology into learning, creating, relevan curricula, and providing professional training for educators. Adequate facilities and infrastructur, commitment to meeting program meed, collaboration and continuous evaluation support this effor. However, training programs, effective financial management, and inclusive learning should help address issues such as educators’ technology skills and student diversity. Thus, MTs Al Ihsan Kalikejambon Tembelang Jombang has great potential ti improve the quality of education in the digital era.